Characterization of Water Extractable Arabinoxylans from a Spring Wheat Flour: Rheological Properties and Microstructure - Alma Campa-Mada; Patricia Torres-Chavez; Jaime Lizardi-Mendoza; Agustín Rascón-Chu; Yolanda López-Franco; Elizabeth Carvajal-Millan; Adriana Morales-Ortega (Molecules, 2013)
In the present study water extractable arabinoxylans (WEAX) from a Mexican spring wheat flour (cv. Tacupeto F2001) were isolated, characterized and gelled and the gel rheological properties and microstructure were investigated. These WEAX presented an arabinose to xylose ratio of 0.66, a ferulic acid and diferulic acid content of 0.526 and 0.036 µg/mg WEAX, respectively and a Fourier Transform Infra-Red (FT-IR) spectrum typical of arabinoxylans. The intrinsic viscosity and viscosimetric molecular weight values for WEAX were 3.5 dL/g and 504 kDa, respectively. WEAX solution at 2% (w/v) formed gels induced by a laccase as cross-linking agent. Cured WEAX gels registered storage (G’) and loss (G’’) modulus values of 31 and 5 Pa, respectively and a diferulic acid content of 0.12 µg/mg WEAX, only traces of triferulic acid were detected. Scanning electron microscopy analysis of the lyophilized WEAX gels showed that this material resembles that of an imperfect honeycomb.